DEVELOPMENT AND IMPROVEMENTS OF COMPUTATIONAL METHODS IMPLEMENTED TO THE COLITEC SOFTWARE - Khlamov, S. V.; Savanevych, V. E.; Briukhovetskyi, O. V.; Dikov, E. N.; Vavilova, I. B. (Одеські астрономічні публікації, 2018)
The CoLiTec software is a large complex of processing modules that implements computational methods for the different purposes: brightness equalization of CCD-frames; automated calibration of the frames by bias-frame, dark-frame, and flat-field for reducing the dynamic range of brightness of the image background; frames track & stack; automated rejection of the anomaly pixels; automated excluding of the objects with anomaly errors; determining the equatorial coordinates of the Solar System small bodies; accurate parameter’s estimation of objects in frames; star’s identification in the frames; astronegative plate’s processing; ensemble differential photometry using comparison stars; determining the instrumental brightness of stars in CCD-frames; automated light curve creation; detection of very slow and very fast objects in series of CCD-frames; detection of objects with a near-zero apparent motion in series of CCD-frames. The described methods work with the different forms of object images (point, long) and during the different observational conditions (with daily telescope guidance and without it). These methods lead to the increasing of astrometry and photometry accuracy indicators as well as the quality indicators for detection of the Solar System small bodies in series of CCD-frames. The CoLiTec software is installed at several observatories of the world. In total, it was used for about 700 000 observations and discovery of more than 1560 asteroids, including five NEO, four comets (C/2011 X1 (Elenin), P/2011 NO1 (Elenin), C/2012 S1 (ISON), and P/2013 V3 (Nevski)), 21 Trojan asteroids of Jupiter, and one Centaur. The paper deals with the CoLiTec software 1) to process the different types of astroinformation, which can be fed on-line in different forms, for example, files stream and video stream, astroplates; 2) to decide the data saving problem at various servers and virtual observatories sites; 3) to improve computational methods and algorithms for automated detection of Solar System small objects; 4) to improve the accuracy of astrometry/photometry reduction.